Air-vent layouts and water-air flow behaviors of a wide spillway aerator. Issue 2 (March 2019) - Yang, James; Teng, Penghua; Lin, Chang
Highlights: An unconventionally wide spillway aerator with representative air-vent arrangements. Appreciable influences of vent layouts on the aerator flow, giving rise to reciprocal adjustment between the jet trajectory and air-flow behaviours of the cavity. Telling difference in aerator performance between the near-wall region and the central part of the flow. Segregated air vents with area augment towards the centre comparably superior to the single-vent layouts. Abstract: A spillway aerator should guarantee favorable flow conditions in the coupled water-air system even if the aerator is unconventionally wide. Eight air-vent configurations are devised and incorporated into a 35-m wide chute aerator for a generalized study. Computational fluid dynamics (CFD) simulations are performed to explore their effects on water-jet and air-cavity features. The Re-normalisation group (RNG) k – ɛ turbulence model and the two-fluid model are combined to predict the two-phase flow field. The results demonstrate appreciable influences of the vent layouts on the water-air flow. The air vents stir the air motion and re-distribute the cavity air pressure. Once the vent layout is modified, reciprocal adjustments exist between the jet behavior and air-pressure field in the cavity, thus leading to considerable differences in air-flow rate, jet-trajectory length, vent air-flow distribution across the chute, etc. The large width plays a discernable role in affecting the aerated flow. Telling differences exist between the near-wall region and the central part of the chute. To improve the duct pressure propagation, a gradual augment of the vent area should be assigned towards the chute center. Relative to single-slot vents across the flow, the layouts with segregated vents gain by comparison. A designer should see to it that a vented aerator operates satisfactorily for a given range of flow discharges.